INFLUENCE OF HYDROGEN ADDITIVE TO FUEL, ON INDICATOR AND EFFECTIVE PARAMETERSAUTOMOBILE ICE - N. G. Pevnev; V. V. Ponamarchuk (Вестник СибАДИ, 2017)
The idea that use of hydrogen as the initiating component to the main fuel, leads to increase in indicator and effective indices of ICE is justified. Special attention is paid to physical and chemical properties of hydrogen and its role when burning in the combustion chamber. In article the example of theoretical calculation of parameters of a working body and calculation of separate indicator and effective parameters is carried out. Calculation is made for the petrol four-stroke engine with the distributed injection of fuel and electronic control by a feed system and ignitions, in case of different percentage ratios of gasoline and hydrogen. Results of calculations are analyzed.